Quality of Life and its Associated Factors among Home-Dwelling Older People - Sattam Shaleh Falah Alotaibi , Moataz Ali Abdullah Alharthi , Aliaa SaidAli Alzharani , Ahmed Abdullah Sahli Al-Ruwais Al-Otaibi , Abeer Gaed Alotibi; Amal Hamad Alhassoon , Mansour Muhammad Al-Mansour , Mona Rafi Al-Amri , Fahad awadh alghdhbani , AbdulazizJaad Saqer Al Osaimi , Ahmed Talal Ojemy (Migration Letters, 2022)
Background: Quality of life (QoL) among older persons provides valuable insights into the potential modifiable risk factors that affect well-being in later life. The study aims: To explore the factors affecting overall and domain-specific (physical health, psychological health, social relationships, and environmental) quality of life (QOL) of home-dwelling older residents in KSA. Methods: A community-based cross-sectional study was carried out from January to July 2022. A representative sample (n=723) of older adults aged >65 years was obtained by the multistage cluster sampling technique. QOL was assessed using the validated Sinhala version of the WHOQOL BREF Questionnaire. Data analysis was done using SPSS V.28. Results: The mean ± SD age was 72.23±6.3 years with the overall QOL score being (mean ± SD) 56.73±12.57/100. The mean ± SD QOL scores of physical health, psychological health, social relationships, and environmental domains were 55.81±15.80, 59.25±14.68, 46.36±20.08 and 64.61±11.96, respectively. The overall QOL in the adjusted model showed a significant positive association with educational status, living conditions (with a spouse, with spouse and children), participation in religious activities, being visited by friends or relatives, and financial independence. The overall QOL was negatively associated with limitations in activities of daily living and instrumental activities of daily living, chronic arthritis, and heart disease in the adjusted model. Living with the spouse was positively associated with the psychological domain of QOL. Osteoporosis and chronic arthritis affected the physical health domain, while cancer and disabling stroke affected the psychological domain of QOL negatively. All statistical significances were considered at p<0.05. Conclusion: The overall QOL of home-dwelling elders of the Colombo District is moderate, with the lowest score being in social relationships and the highest in the environmental domain. Educational status, engaging in religious activities, and financial independence are key factors associated with a better QOL. Limitations in physical activity and chronic diseases are associated with a reduced QOL. Living with the spouse is a key factor associated with the psychological health domain.